The Influence of Leadership and Work Environment on the Performance of Bawaslu Employees in South Sumatra Province - Shandika, Sisfalbi Defri; Hasmawaty, Hasmawaty (Yayasan Sembilan Pemuda Indonesia, 2024)
An institution’s human resources are one of its most valuable resources. since it is a component of an establishment. The institution must possess excellent human resources and be able to effectively and responsibly manage employee performance to ensure that it aligns with the institution’s goals for its objectives to be met. The longevity of an institution is entirely the responsibility of its leader and plays a critical part in it. Every leader needs to be able to adjust his style of leadership to fit the circumstances of the moment. The province of South Sumatra’s Bawaslu (election supervisory body) is now evaluating its leadership. Owing to the growing frequency of general elections, which calls for leaders who can build strong bonds with their staff, the Provincial Bawaslu leadership style has adopted an authoritarian approach in which the leadership style consistently dominates the organization. Achieving the outcomes of a person’s or employee’s labor in accomplishing organizational goals is known as increasing employee performance. A lack of time discipline at work, such as workers who arrive late or leave early, indicates that the level of employee attendance at work is still below ideal, according to the pre-survey data. This study employs a non-probability sampling technique combined with a quantitative approach. The 283 workers at the Bawaslu Offices spread over South Sumatra made up the study’s population. One hundred persons made up the study’s sample. The findings of this study suggest that: (1) Work Environment has a substantial impact on performance; (2) Leadership has a big impact on performance; and (3) Leadership and Work Environment both have a considerable impact on employee performance.